Learning to choose : stories and essays about science, technology, and human values - Goldberg, Lazer (New York : Scribner, 1976)
Stories and essays designed to provoke ethical questions and provide the opportunity to choose courses of action that will have consequences affecting our own well-being and the well-being of the rest of the world.
Keywords: Decision -- Making (Ethics) -- Juvenile literature; Children -- Conduct of life -- Juvenile literature